2021
DOI: 10.1016/j.jtocrr.2020.100105
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of Mobocertinib Highlights the Putative Therapeutic Window of This Novel EGFR Inhibitor to EGFR Exon 20 Insertion Mutations

Abstract: Introduction: EGFR exon 20 insertion mutations account for 10% of all EGFR mutations and are mostly insensitive to approved EGFR tyrosine kinase inhibitors (EGFR TKIs). Novel EGFR TKIs have been developed or repurposed for these mutants. A limited number of preclinical studies have detailed these EGFR TKIs. We sought to use commercially available mobocertinib (TAK-788) to characterize the preclinical therapeutic window of this EGFR TKI against EGFR mutations and to probe possible on-target mechanisms of resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Studies showed that exon 20 mutations are heterogenous in their response to TKIs 10,22 . Insertions in the αC-helix (for example, an FQEA insertion at A763 (A763insFQEA)) were pan-sensitive to EGFR TKIs 23,24 , whereas those in the loop following the αC-helix (A767-C775) were not 25,26 , and the T790M mutation was sensitive to third-but not first-or second-generation TKIs. We found that most exon 20 point mutations were PACC mutations; that exon 20 insertions in the αC-helix were classical-like mutations; and, that the remainder of exon 20 insertions occurring in the C-terminal loop of the αC-helix were a distinct subgroup: exon 20 loop insertions (Ex20ins-L) (Fig.…”
Section: Exon 20 Mutations Are Heterogenousmentioning
confidence: 99%
“…Studies showed that exon 20 mutations are heterogenous in their response to TKIs 10,22 . Insertions in the αC-helix (for example, an FQEA insertion at A763 (A763insFQEA)) were pan-sensitive to EGFR TKIs 23,24 , whereas those in the loop following the αC-helix (A767-C775) were not 25,26 , and the T790M mutation was sensitive to third-but not first-or second-generation TKIs. We found that most exon 20 point mutations were PACC mutations; that exon 20 insertions in the αC-helix were classical-like mutations; and, that the remainder of exon 20 insertions occurring in the C-terminal loop of the αC-helix were a distinct subgroup: exon 20 loop insertions (Ex20ins-L) (Fig.…”
Section: Exon 20 Mutations Are Heterogenousmentioning
confidence: 99%
“…Mobocertinib (TAK‐788, AP32788) is a potent, selective orally administered inhibitor of epidermal growth factor receptor (EGFR) and human epidermal growth factor 2 including exon 20 insertion mutations, 1 for which there are no effective approved tyrosine kinase inhibitors (TKIs). It potently inhibits all activated forms of the EGFR gene, including those containing exon 20 activating insertion mutations, uncommon activating mutations, and the common activating mutations (exon 19 deletions and L858R) with or without the T790M resistance mutation 1,2 . An iterative, structure‐guided design strategy was used to optimize affinity and selectivity for EGFR with exon 20 insertion mutations over wild‐type EGFR , thereby differentiating it from available TKIs that are typically ineffective against EGFR exon 20 insertion mutations 1 .…”
mentioning
confidence: 99%
“…It potently inhibits all activated forms of the EGFR gene, including those containing exon 20 activating insertion mutations, uncommon activating mutations, and the common activating mutations (exon 19 deletions and L858R) with or without the T790M resistance mutation. 1 , 2 An iterative, structure‐guided design strategy was used to optimize affinity and selectivity for EGFR with exon 20 insertion mutations over wild‐type EGFR , thereby differentiating it from available TKIs that are typically ineffective against EGFR exon 20 insertion mutations. 1 Accumulating preclinical data support that mobocertinib is neither mutagenic nor genotoxic, and clinical data indicate that generally mild adverse events have been reported within the single‐dose range of 20‐160 mg in clinical pharmacology studies conducted in healthy participants (data on file; Millennium Pharmaceuticals, Inc., Cambridge, Massachusetts).…”
mentioning
confidence: 99%
“…Therapeutic options for patients with NSCLC whose tumors harbor EGFR exon 20 insertion mutations or HER2 ‐activating mutations are limited. Mobocertinib (TAK‐788; ARIAD Pharmaceuticals, Inc, a wholly owned subsidiary of Takeda Pharmaceutical Company Limited, Cambridge, Massachusetts), a novel, investigational, next‐generation TKI, has potent preclinical inhibitory activity against activating EGFR and HER2 mutations, including exon 20 insertions, and demonstrates stronger inhibition of these variants than wild‐type (WT) EGFR 16 . In an ongoing first‐in‐human phase 1/2 study of mobocertinib (NCT02716116), preliminary data indicated a median time to maximum plasma concentration (t max ) of 4 hours, and dose‐proportional maximum plasma concentration (C max ) and area under the concentration‐time curve (AUC) from time 0 to 24 hours.…”
mentioning
confidence: 99%
“…Mobocertinib (TAK‐788; ARIAD Pharmaceuticals, Inc, a wholly owned subsidiary of Takeda Pharmaceutical Company Limited, Cambridge, Massachusetts), a novel, investigational, next‐generation TKI, has potent preclinical inhibitory activity against activating EGFR and HER2 mutations, including exon 20 insertions, and demonstrates stronger inhibition of these variants than wild‐type (WT) EGFR . 16 In an ongoing first‐in‐human phase 1/2 study of mobocertinib (NCT02716116), preliminary data indicated a median time to maximum plasma concentration (t max ) of 4 hours, and dose‐proportional maximum plasma concentration (C max ) and area under the concentration‐time curve (AUC) from time 0 to 24 hours. On repeat dosing at 160 mg once daily, accumulation ratio of mobocertinib AUC from time 0 to 24 hours on cycle 2 day 1 over cycle 1 day 1 was 1.03, which is smaller than the calculated accumulation ratio based on its terminal half‐life and dose interval, suggesting autoinduction of mobocertinib apparent oral clearance via induction of cytochrome P450 (CYP) 3A at and above the 160‐mg dose.…”
mentioning
confidence: 99%